Et Tu, U2?: "Wake Up Dead Man" and Bono's Perceived Betrayal of the Faith - Holm-Hudson, Kevin (Journal of religion and popular culture, 2007)
In one of U2's most controversial songs, "Wake Up Dead Man," from 1997's Pop album, singer-lyricist Bono seemingly portrayed a dead and powerless Jesus, unable to help a troubled world. This interpretation assumes the song to be an autobiographical spiritual statement, the legacy of the perceived "sincerity" of 1970s singer-songwriters. But was Bono portraying a musical persona? Drawing upon Edward T. Cone's persona theory as well as the writings of C. S. Lewis, Francis Schaeffer, N. T. Wright and Christian Kettler, "Wake Up Dead Man" is interpreted as a dialogue, rather than as a diatribe.